'I Kinda Like to Go Off the Track': Finding David Lynch in the Middle World of Dune. (3rd April 2021) - Amadio, David
Abstract: For many scholars of David Lynch's work, Dune is considered a spectacular failure, a costly creative misstep on the way to Blue Velvet . While it may not be regarded as one of his signature films, Dune contains enough of Lynch's creative personality to warrant a critical re-examination. The purpose of this study is to place Dune within the context of his earlier work, namely Eraserhead and The Elephant Man, and to mine it for those tropes with which Lynch has become synonymous: enabling the grotesque, interiority and the unconscious mind, and the relationship between industry and flesh. By the director's own admission, Dune forced him into an aesthetic middle world, wedging him between the midnight movie and mainstream cinema. Using Thomas Leitch's theory of adaptation in both an archival and teleological reading of Dune, I demonstrate how Lynch asserts himself in this middle world, how he succeeds in honouring the source material while also meeting his authorial desire to reinvent it, to decouple from the archive and 'go off the track'.